Inovativni pristopi z uporabo radarja hitrosti in ostale tehnologije za individualni napredek učencev pri predmetu šport v III. triadi - Krevh, Alojz (Revija inovativna pedagogika, 2025)
Innovative approaches to teaching physical education (PE) are crucial to promoting equal opportunities and active participation for all learners. This article is aimed at PE teachers in primary school who are open to innovative methods in their work. In a PE lesson in Grade 8, we covered the topic of handball, where the focus was on the shot on goal. The working methods used (individualization, differentiation, use of digital technology) allow the content to be adapted to the pupils so that each pupil is active and progresses at their level of ability. Pupils need a computer background for the lessons to run smoothly and effectively. Depending on the purpose of the learning, pupils logged into the online PE classroom using their mobile phones and followed the online learning path. They used the Padlet and Copilot apps to consolidate their prior knowledge and share the information on the interactive screen. In the main part, they measured the speed of the ball with the help of a "radar". Based on the measured speed of flight of the ball, we calculated the time taken for the ball to travel to the goal. We integrated the content of PE with the subject of physics to facilitate the understanding of physical quantities. In addition to developing competencies in sharing digital content, we worked with the pupils to develop basic computer science skills in data analysis and processing. The aim was to present the data and monitor their progress in the goal kick technique. This allowed the pupils to be team-oriented and motivated during the lesson and to improve their skills through real-time teacher feedback.
Keywords: analiza in obdelava podatkov; cross-curricular approach; data analysis and data processing; data sharing; deljenje podatkov; digital technology; Digitalna pismenost; digitalna tehnologija; medpredmetno povezovanje; Osnovnošolsko izobraževanje; spodbudno učno okolje pri športu; stimulating learning environment in physical education; Športna vzgoja